Досвід Сполучених Штатів Америки у сфері організації взаємодії органів досудового розслідування - Коломієць, Вадим Іванович (Протидія дезінформації в умовах російської агресії проти України: виклики і перспективи: тези доп. учасників міжн. наук.-практ. конф. (Анн-Арбор - Харків, 12-13 груд. 2023 р.), 2023)
The author singles out the elements of the organization of cooperation between the pretrial investigation bodies of the USA, which should be used in Ukrainian realities: 1) create conditions under which various law enforcement agencies in the process of solving complex cases can independently combine their resources, in particular: economic, human, technological; 2) to develop a single information system that will combine information on crimes, wanted persons and objects, as well as on weapons and drugs; 3) to develop an effective system of distribution of competence between various subjects of interaction of pre-trial investigation, which should be built taking into account the specifics of the levels of the corresponding joint activity.